SYSTEMATIC LITERATURE REVIEW ON PEER-TO-PEER LENDING: A COMPARISON BETWEEN TRADITIONAL LENDING AND DECENTRALIZED FINANCE MODELS - Ni Gusti Ayu Pitria; Winola Wijayanti; Grace T. Pontoh; Aini Indrijawati (Jurnal Bisnis dan Akuntansi, 2024)
This research aims to conduct a comparative study between the peer-to-peer lending system and the traditional loan model. The method used is a systematic literature review study of 61 relevant scientific papers published between 2015 and 2024. The parameters analyzed include the provision of access to finance, transaction costs, the speed of the lending process, as well as the level of transparency and consumer protection. The results show that the peer-to-peer lending system has advantages in terms of providing easier and faster access to financing for individuals and small businesses because it uses a simple and uncomplicated digitization process. This model is also able to reduce transaction costs and speed up the process through the application of blockchain technology that streamlines the flow of transactions. The study also found that blockchain technology supporting peer-to-peer lending plays an important role in increasing the transparency of transactions through decentralized digital records that cannot be manipulated. However, the challenges of immature financial regulations and rapidly evolving cybersecurity risks still need to be addressed to support the wider adoption of peer-to-peer lending as a new alternative in the financial services industry. Therefore, further research is needed to find solutions to these barriers so that peer-to-peer lending can be optimally utilized as an inclusive future financial solution.